Association between vitamin C intake and thyroid function among U.S. adults: a population-based study - Jie Wu; Chuyu Jia; Qiang Wang; Xin Li (Frontiers in Endocrinology)
BackgroundAlthough some evidence suggests a role for vitamin C intake in thyroid diseases, the complex interplay between vitamin C intake and thyroid function remains incompletely understood. The objective of this study was to explore the relationship between vitamin C intake and serum thyroid function in the United States adults.MethodsA total of 5,878 participants from the National Health and Nutrition Examination Survey (NHANES) between 2007 and 2012 were included in this study. Weighted multivariate linear regression models, subgroup analyses, and interaction terms were used to assess the association between vitamin C intake, evaluated as a continuous and categorical variable, and thyroid function. Additionally, restricted cubic spline (RCS) regression was employed to assess any nonlinear relationship that may exist between vitamin C intake and thyroid function.ResultsAfter adjusting for covariates, our research found a significant inverse correlation between vitamin C intake and total thyroxine (TT4) (β= -0.182, P= 0.006). Using subgroup analyses, the association was more pronounced among subjects with lower alcohol consumption(β= -0.151, P=0.013, P for interaction = 0.043). In RCS regression, the correlation between vitamin C and TT4 exhibited a distinct reversed L-shaped curve pattern in total participants (P for nonlinear = 0.005) and male adults (P for nonlinear = 0.014). Additionally, we found an inverted U-shaped curve pattern in the relationship between vitamin C intake and FT4 (P for nonlinear = 0.029), while an U-shaped curve relationship was observed between vitamin C consumption and the FT3/FT4 ratio (P for nonlinear = 0.026).ConclusionThe findings of our study have illustrated a notable correlation between vitamin C intake and thyroid function. A high level of vitamin C intake is associated with a decreased in TT4 levels among American adults, and the association was more pronounced among subjects with lower alcohol consumption. Furthermore, our analysis revealed a nonlinear correlation between the intake of vitamin C and the levels of TT4, FT4, and FT3/FT4 ratio. Our findings support the rationale for making food-based dietary recommendations and maybe provide guidance for diet guidelines with thyroid dysfunction to a certain extent in the future.